Doxycycline‐Induced Expression of Transgenic Human Tumor Necrosis Factor α in Adult Mice Results in Psoriasis‐like Arthritis1. Issue 9 (26th August 2013) - Retser, Eugen; Schied, Tanja; Skryabin, Boris V.; Vogl, Thomas; Kanczler, Janos M.; Hamann, Nina; Niehoff, Anja; Hermann, Sven; Eisenblätter, Michel; Wachsmuth, Lydia; Pap, Thomas; van Lent, Peter L. E. M.; et al.
<x xml:space="preserve">Abstract</x> Objective To generate doxycycline‐inducible human tumor necrosis factor α (TNFα)–transgenic mice to overcome a major disadvantage of existing transgenic mice with constitutive expression of TNFα, which is the limitation in crossing them with various knockout or transgenic mice. Methods A transgenic mouse line that expresses the human TNFα cytokine exclusively after doxycycline administration was generated and analyzed for the onset of diseases. Results Doxycycline‐inducible human TNFα–transgenic mice developed an inflammatory arthritis– and psoriasis‐like phenotype, with fore and hind paws being prominently affected. The formation of "sausage digits" with characteristic involvement of the distal interphalangeal joints and nail malformation was observed. Synovial hyperplasia, enthesitis, cartilage and bone alterations, formation of pannus tissue, and inflammation of the skin epidermis and nail matrix appeared as early as 1 week after the treatment of mice with doxycycline and became aggravated over time. The abrogation of human TNFα expression by the removal of doxycycline 6 weeks after beginning stimulation resulted in fast resolution of the most advanced macroscopic and histologic disorders, and 3–6 weeks later, only minimal signs of disease were visible. Conclusion Upon doxycycline administration, the doxycycline‐inducible human TNFα–transgenic mouse displays the major features of inflammatory arthritis. It represents a unique animal model for studying the molecular mechanisms of arthritis, especially the early phases of disease genesis and tissue remodeling steps upon abrogation of TNFα expression. Furthermore, unlimited crossing of doxycycline‐inducible human TNFα–transgenic mice with various knockout or transgenic mice opens new possibilities for unraveling the role of various signaling molecules acting in concert with TNFα.